Sierpiński’s Philosophy of Mathematics - Lewandowska, Katarzyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
The main aim of the paper was to draw attention to Wacław Sierpiński as not only a great mathematician but also a philosopher. We undertook the attempt of reconstruction of Sierpiński’s philosophy. To aim this goal we mainly based ourselves on Sierpiński’s habilitation lecture entitled The concept of correspondence in mathematics. The complementation of Sierpiński’s philosophical views were conclusions from his mathematical achievements, his scheme of research on The Axiom of Choice, and his attitude to this axiom.